Norway : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation for Norway highlights that the mainland GDP growth edged up to an estimated 1.4 percent in 2002, from 12 percent in 2001, driven by strong consumption growth. Mainland investment and traditional exports slackened, as a result of weak external demand, high real interest rates, and an appreciation of the nominal effective exchange rate by 11.5 percent during 2002. Unemployment remained fairly stable through 2002 as the expansion of the sheltered sector offset employment losses in the exposed sector.